A Study of the business operations of the UPHMO a management study - De Leon, Agnes Rosario A.
The UPHMO is a community pilot project established with the expectation that prepaid managed health care at the community level could be financially viable in providing middle and low income families with better access to health care.~~~WHY THIS STUDY: This study of the business operation of the UPHMO was done to determine whether the expectation of financial viability was realized, to identify areas that need improvement, and to propose recommendations which the organization can use for improvement.~~~~METHODOLOGY & LIMITATIONS: The methods used in the study consisted of review of pertinent documents such as previous studies, financial statements and interviews with HMO experts, UPHMO key officers, staff and enrollees.~~~~There was lack of vital statistical data and annual reports on performance, minutes of business meetings and other documents which could have yielded significant information to the study.~~~~FINDINGS AND ANALYSIS: Five years after it started operations in 1989 with 89 members, the UPHMO now has a current enrollment of 920 members, a rather slow growth. The organization is in a precarious situation faced with the following problems: ...
Thesis (Master of Hospital Administration) -- University of the Philippines Manila
Keywords: Health maintenance organizations